2021
DOI: 10.3390/catal11040439
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Regioselective Suzuki Coupling of 2,4-Dichloropyrimidines with Aryl and Heteroaryl Boronic Acids

Abstract: Suzuki coupling reaction has been often used for the preparation of a diverse set of substituted pyrimidines. In this study, the Suzuki coupling of 2,4-dichloropyrimidines with aryl and heteroaryl boronic acids was investigated. A thorough screening of reaction conditions and the use of microwave irradiation led to a very efficient and straightforward synthetic procedure providing C4-substituted pyrimidines in good to excellent yields. Short reaction time (15 min) and extremely low catalyst loading (0.5 mol%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
2
0
4
Order By: Relevance
“…The reaction of aryl chlorides with aryl neopentyl esters afforded products in up to 91% yield. The same authors also found a pre-transmetalation Pd-O-B intermediate A microwave-assisted regioselective SM coupling of 1,4dihydropyridines and aryl/heteroaryl boronic acid using Pd(PPh3)4 (0.5 mol%) was reported by Sova et al 30 The reaction was completed within 15 mins under the microwave irradiation conditions at 100 °C. This reaction afforded C4-substituted pyrimidines.…”
Section: Template For Synthesis Thiemesupporting
confidence: 55%
“…The reaction of aryl chlorides with aryl neopentyl esters afforded products in up to 91% yield. The same authors also found a pre-transmetalation Pd-O-B intermediate A microwave-assisted regioselective SM coupling of 1,4dihydropyridines and aryl/heteroaryl boronic acid using Pd(PPh3)4 (0.5 mol%) was reported by Sova et al 30 The reaction was completed within 15 mins under the microwave irradiation conditions at 100 °C. This reaction afforded C4-substituted pyrimidines.…”
Section: Template For Synthesis Thiemesupporting
confidence: 55%
“…İlk defa 1996 yılında mikrodalga desteği SM tepkimelerinde kullanılmış olup [41] şaşırtıcı etkisi nedeniyle sonrasında birçok eşleşme tepkimelerinde destekleyici teknik olarak kullanılmıştır [42,43]. Suzuki-Miyaura tepkimelerinde mikrodalga ısıtma ile geleneksel ısıtma kıyaslandığında tepkime verimleri yakın olduğu halde tepkime süreleri saatlerden dakikalara hatta saniyelere düşmektedir [44][45][46][47]. Bu yüzden mikrodalga destekli tepkimelerin ileriki yıllarda sayısının artacağını öngörmek zor değildir.…”
Section: Mikrodalga Destekli Tepkimelerde Sentez Kolaylığıunclassified
“…İlk defa 1996 yılında mikrodalga desteği SM tepkimelerinde kullanılmış olup [41] şaşırtıcı etkisi nedeniyle sonrasında birçok eşleşme tepkimelerinde destekleyici teknik olarak kullanılmıştır [42,43]. Suzuki-Miyaura tepkimelerinde mikrodalga ısıtma ile geleneksel ısıtma kıyaslandığında tepkime verimleri yakın olduğu halde tepkime süreleri saatlerden dakikalara hatta saniyelere düşmektedir [44][45][46][47]. Bu yüzden mikrodalga destekli tepkimelerin ileriki yıllarda sayısının artacağını öngörmek zor değildir.…”
Section: Mikrodalga Destekli Tepkimelerde Sentez Kolaylığıunclassified